Malaria in Birmingham and a London teaching hospital. Issue 6160 (10th February 1979) - Ellis, C J; Eykyn, S J; Watkins, P; Bell, M; Geddes, A M
Abstract : During the past five years the incidence of imported malaria increased among patients seen in East Birmingham Hospital and in St Thomas's Hospital, London. Plasmodium vivax was the predominant species in Birmingham, and was almost always acquired by Asian immigrants visiting the Indian subcontinent. In St Thomas's P falciparum was most commonly imported, usually by African immigrants visiting Nigeria and Ghana. Two patients (one Irish, one Japanese) died of falciparum malaria after visiting tropical Africa. In both hospitals the immigrant patients had seldom taken prophylactic drugs, and the few who had, ceased to do so on arrival in the UK and sometimes before leaving the malarious country. Apparently immigrants who visit their homeland do not consult their general practitioners before travelling, are given inappropriate advice, or do not take appropriate advice when given. Since the incidence of imported falciparum malaria in the UK is rising, the following points should be considered: the infection may be lethal, particularly in patients lacking immunity; it can mimic other diseases, which may lead to delayed diagnosis; severe disease may be associated with few parasites on a blood film, and even if the result is negative further tests should be performed; clinicians and hospital pharmacists should be aware of the need to keep permanent stocks of parenteral chloroquine and quinine preparations.